2005
DOI: 10.1016/j.jacc.2004.09.068
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of selectin function attenuates microvascular platelet deposition and platelet-mediated myocardial injury after transient ischemia

Abstract: The results suggest that selectin-dependent adhesion is a prominent mechanism of platelet deposition in reperfused cardiac microvessels and highlight its potential as a therapeutic target in patients with acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 29 publications
3
54
0
3
Order By: Relevance
“…19 -21 Experimental studies have shown that ischemia-reperfusion triggers platelet aggregation within coronary vessels that can be inhibited by interventions such as deletion of P-selectin or the intracellular adhesion molecule-1gene. [22][23][24] In our study, platelet accumulation in the mouse infarcted myocardium is unique in its largely extravascular location, early presence, and close association with infiltrated inflammatory cells. How do circulating platelets enter into the interstitial space of the infarcted myocardium?…”
Section: Discussionmentioning
confidence: 95%
“…19 -21 Experimental studies have shown that ischemia-reperfusion triggers platelet aggregation within coronary vessels that can be inhibited by interventions such as deletion of P-selectin or the intracellular adhesion molecule-1gene. [22][23][24] In our study, platelet accumulation in the mouse infarcted myocardium is unique in its largely extravascular location, early presence, and close association with infiltrated inflammatory cells. How do circulating platelets enter into the interstitial space of the infarcted myocardium?…”
Section: Discussionmentioning
confidence: 95%
“…36,37 In addition, it blocks selectin-induced leukocyte and platelet accumulation to ischemic artery and prevent further damage and thrombosis. 38,39 In isolated endothelial cells, fucoidan is found to block the formation of capillary-like structures (tubes) by the endothelial cells, 14 inhibit adhesion of sickle erythrocytes to endothelium, 40 and attenuate endothelium-mediated angiogenesis. 41 Moreover, fucoidan also modulates proliferation and migration of human endothelial cells, suggesting a potential role of fucoidan as a new therapeutic agent for vascular endothelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…[109][110][111][112][113][114][115] Such aggregates are either released from the epicardial atherosclerotic culprit lesion and dislodged into the microcirculation or formed in the coronary microcirculation. These cellular aggregates contribute to the impairment of microvascular perfusion.…”
Section: Stasis and Intravascular Cellular Aggregatesmentioning
confidence: 99%